Frontal fibrosing alopecia: A review of disease pathogenesis - Miao, Yu-Jie; Jing, Jing; Du, Xu-Feng; Mao, Mei-Qi; Yang, Xiao-Shuang; Lv, Zhong-Fa (Frontiers in Medicine, 2022)
Frontal fibrosing alopecia (FFA) is a primary patterned cicatricial alopecia, which mostly affects postmenopausal women and causes frontotemporal hairline regression and eyebrow loss. Although the incidence of FFA has been increased worldwide over the last decade, its etiology and pathology are still unclear. We cover the latest findings on its pathophysiology, including immunomodulation, neurogenic inflammation, and genetic regulation, to provide more alternatives for current clinical treatment. Persistent inflammatory response and immune privilege (IP) collapse develop and lead to epithelial hair follicle stem cells (eHFSCs) destruction and epithelial-mesenchymal transition (EMT) in the bulge area, which is the key process in FFA pathogenesis. Eventually, fibrous tissue fills the entire hair follicle (HF). In addition, some familial reports and genome-wide association studies suggest a genetic susceptibility or epigenetic mechanism for the onset of FFA. The incidence of FFA increases sharply in postmenopausal women, and many FFA patients also suffer from female pattern hair loss in clinical observation, which suggests the potential association between FFA and steroid hormones. Sun exposure and topical allergens may be also triggers of FFA, but this conjecture has not been proven. More evidence and cohort studies are needed to help us understand the pathogenesis of this disease.